1 Sudden Arrhythmic Death Syndrome (sads): Diagnostic Yield of Comprehensive Clinical Evaluation of Paediatric First-degree Relatives. (31st May 2014) - Spanaki, Adriani; Giudici, Valentina; Hendry, Val Jennifer; Mead-Regan, Sarah; Field, Ella; Bryant, Rory; Ralph, Jessica; Abrahms, Dominic; Lowe, Martin; Kaski, Juan Pablo
Abstract : Background: Sudden arrhythmic death syndrome (SADS) is most often caused by heritable cardiac diseases. Studies in adults have identified evidence of inherited cardiovascular diseases in up to 53% of families, but data on the prevalence of familial disease in children are scarce. The aim of this study was to evaluate the yield of clinical screening in paediatric first-degree relatives of victims of SADS or aborted cardiac arrest (ACA) using a systematic and comprehensive protocol. Methods: All consecutive paediatric patients referred for family screening between 2003 and 2013 after a SCD or ACA of a family member were retrospectively enrolled into the study. Systematic evaluation of the children included clinical examination, family history, ECG, echocardiogram, 24-hour tape and signal averaged ECG. Older patients also underwent exercise testing, cardiac MRI and ajmaline provocation testing. Results: A total of 110 children from 63 consecutive families were included in the study. An inherited cardiac disease was identified in 12 1 st -degree children from 11 (17.5%) families (7 children were diagnosed with Brugada syndrome, 2 with long QT syndrome, 1 with CPVT, and 2 had late potentials on signal averaged ECGs). Conclusions: These data show a high prevalence of inherited heart disease in paediatric first-degree relative in families with a history of SCD or ACA. The results highlight the importance of a systematic, comprehensive approach and ongoing screening of paediatric family members.